2009
DOI: 10.1063/1.3273407
|View full text |Cite
|
Sign up to set email alerts
|

Triplet annihilation exceeding spin statistical limit in highly efficient fluorescent organic light-emitting diodes

Abstract: We have demonstrated that the exemplary red fluorescent organic light-emitting diodes (OLEDs) gain as much as half of their electroluminescence from annihilation of triplet states generated by recombining charge carriers. The magnitude of triplet-triplet annihilation (TTA) contribution in combination with the remarkably high total efficiencies [>11% external quantum efficiency (EQE)] indicates that the absolute amount of electroluminescence attributable to TTA substantially exceeds the limit imposed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
357
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(369 citation statements)
references
References 20 publications
8
357
0
4
Order By: Relevance
“…Because the magnetic field only affects the singlet channel [34], it can be used to examine the competition between the two annihilation channels and determine their relative contributions to TTA. Analysis of time-resolved electroluminescence with and without the magnetic field yielded a 1.3 branching ratio, which is substantially higher than the value of 0.33 expected for a purely statistical annihilation process [29]. Interestingly, the branching ratio obtained in this study of magnetic field effects was in excellent agreement with the observed fraction of TTA-related emission in total electroluminescence.…”
Section: Limits Of Triplet-triplet Annihilation-related Efficiency Ensupporting
confidence: 75%
See 2 more Smart Citations
“…Because the magnetic field only affects the singlet channel [34], it can be used to examine the competition between the two annihilation channels and determine their relative contributions to TTA. Analysis of time-resolved electroluminescence with and without the magnetic field yielded a 1.3 branching ratio, which is substantially higher than the value of 0.33 expected for a purely statistical annihilation process [29]. Interestingly, the branching ratio obtained in this study of magnetic field effects was in excellent agreement with the observed fraction of TTA-related emission in total electroluminescence.…”
Section: Limits Of Triplet-triplet Annihilation-related Efficiency Ensupporting
confidence: 75%
“…However, the observed electroluminescence can be readily understood without invoking any new mechanisms if one notices that the recombination leading to the triplet state of rubrene is not forbidden by energy, and, furthermore, the rubrene triplets readily undergo TTA to generate the emissive singlet state. In fact, by using a similar heterojunction in doped OLEDs resembling highly efficient OLEDs [29], we have been able to construct red-emitting devices operating relatively efficiently at similarly low voltages and demonstrate that their electroluminescence is dominated by the delayed component that shows all typical tell-tale signs of TTA (T. D. Pawlik, D. Y. Kondakov 2009, unpublished data).…”
Section: Limits Of Triplet-triplet Annihilation-related Efficiency Enmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the yield of singlet emissive states is highly dependent on the relative energy order of the excited singlet and triplet energy levels in the molecule, and the maximum total singlet yield is limited to 62.5%. OLEDs with TTA contribution as large as 40% have been demonstrated but the relative merit of this approach is still unsatisfactory [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the yield of singlet emissive states is highly dependent on the relative energy order of the excited singlet and triplet energy levels in the molecule, and the maximum total singlet yield is limited to 62.5%. OLEDs with TTA contribution as large as 40% have been demonstrated but the relative merit of this approach is still unsatisfactory [6,7].The TADF mechanism uses the thermal energy to assist reverse intersystem crossing and promote the up-conversion of lower triplet states into more energetic but emissive singlet states [8]. The efficiency of the TADF mechanism is controlled by two main parameters, the energy splitting between the singlet and triplet states ( E ST ) and the efficiency of non-radiative pathways available for the excited singlet and triplet states to decay [9,10].…”
mentioning
confidence: 99%